Effects of background fertilization followed by co-application of two kinds of bacteria on soil nutrient content and rice yield in Northeast China - Sun, Tao; Liu, Yuyingnan; Wu, Shuang; Zhang, Jizhou; Qu, Bin; Xu, Jinggang (International Journal of Agricultural and Biological Engineering, 2020)
With the improvement of living standards, people pay more and more attention to the quality and safety of rice. Microbial agents are favored by the public because they can activate the nutrient supply in the soil, and reduce the residue and application amount of chemical fertilizers and pesticides. Based on the conventional fertilization in the field, Bacillus mucilaginosus and Aspergillus niger were applied, Bacillus mucilaginosus was inoculated at four levels in the paddy soil in the cold region of Heilongjiang Province of China. The effects of different proportions of Bacillus mucilaginosus and Aspergillus niger on the number of soil microorganisms, enzyme activity, microbial biomass, soil biochemical intensity, soil nutrient content, plant nutrient content and yield were studied, and the effects on the plant nutrient content of rice and the nutrient dynamics were discussed. The results showed that a 2.62%-21.20% higher yield of rice obtained from co-application treatments compared with that of the control-blank treatment. Furthermore, the highest yield obtained (10736±65 kg/hm2) suggested that the optimized values for the two bacteria applied were 120×1011 CFU/hm2 for Bacillus mucilaginosus and 15×1011 CFU/hm2 for Aspergillus niger. Bacillus mucilaginosus can decompose minerals in soil, dissolve potassium and silicon, decompose apatite and release phosphorus into soil. Aspergillus niger can transform the phosphate which cannot be absorbed by plants into soluble phosphate which can be directly absorbed by plants by producing non-volatile acids. In particular, Bacillus mucilaginosus and Aspergillus niger have synergistic effect, and their combined application effect is greater than that of two bacteria alone. Co-application promoted the release of soil soluble silicon, and then increased the silicon content of plants. At the same time, soil microorganism, microbial biomass, enzyme activity and biochemical activity all increased significantly. This study provides an effective way to reduce the amount of chemical fertilizer applied in rice production in cold regions of China. Keywords: microbial inoculants, microbial fertilizer, rice, co-application, Bacillus mucilaginosus, Aspergillus niger, nutrients DOI: 10.25165/j.ijabe.20201302.4863 Citation: Sun T, Liu Y Y N, Wu S, Zhang J Z, Qu B, Xu J G. Effects of background fertilization followed by co-application of two kinds of bacteria on soil nutrient content and rice yield in Northeast China. Int J Agric & Biol Eng, 2020; 13(2): 154–162.